TYPIFICATION OF LITHOGENESIS AND ORE-FORMATION STAGES - KURYLO, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Problems of typification of ore-formation stages are considered in connection with development of sedimentary and sedimentary- metamorphosed rocks. The typification is based on ores substance source, types and stages lithogenesis. Diagenetic, catagenetic, metagenetic and metamorphic deposits are defined.